2012
DOI: 10.1177/1359105312452314
|View full text |Cite
|
Sign up to set email alerts
|

A brief motivational intervention for heavy alcohol use in dental practice settings: Rationale and development

Abstract: Although brief alcohol interventions have proven effective in a variety of health care settings, the present article describes the development of the first brief intervention for heavy drinkers in dental practice. Elements of motivational interviewing and personalized normative feedback were incorporated in a 3- to 5-minute intervention delivered by dental hygienists. The intervention is guided by a one-page feedback report providing personalized normative feedback regarding the patient’s current oral health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…37 Access to additional unstructured clinical data from encounter notes may also increase the sensitivity of natural language processing to other important health conditions, such as tobacco use. 38,39 Chairside screening interventions for chronic diseases including substance use disorders, 40 eating disorders, 41 cardiovascular disease, 42 diabetes, 43 and obesity 44 have all been validated, but appropriate referral of patients found to be at high risk has been described as a hurdle. 45 While not explored as part of this study, automated sharing of these results with patients' medical teams would allow for ideal patient management and prompt referral to necessary providers.…”
Section: Discussionmentioning
confidence: 99%
“…37 Access to additional unstructured clinical data from encounter notes may also increase the sensitivity of natural language processing to other important health conditions, such as tobacco use. 38,39 Chairside screening interventions for chronic diseases including substance use disorders, 40 eating disorders, 41 cardiovascular disease, 42 diabetes, 43 and obesity 44 have all been validated, but appropriate referral of patients found to be at high risk has been described as a hurdle. 45 While not explored as part of this study, automated sharing of these results with patients' medical teams would allow for ideal patient management and prompt referral to necessary providers.…”
Section: Discussionmentioning
confidence: 99%
“…The test group showed only minimal improvement in child feeding practices and nighttime bottle habits. Given the success MI has shown in the area of behavior change, we expected different results [17][18][19]. Yet, research studies conducted after ours show a growing body of evidence that an increase in knowledge does necessarily result in sustained behavior change, especially in high risk populations.…”
Section: Discussionmentioning
confidence: 81%
“…MI is a patient-centered, collaborative counseling approach designed to strengthen an individual's intrinsic motivation towards a positive behavior change [16]. Motivational interviewing (MI) has emerged as a successful strategy to address undesirable behaviors such as unhealthy eating habits, lack of exercise, and smoking and alcohol use [17][18][19]. MI focuses on an individual-provider partnership and is based on the premise that an individual's reasons for change and autonomy to make their own decisions should be supported by the provider [16].…”
Section: Introductionmentioning
confidence: 99%
“…10 Neff et al reported that 75% of dentists (n=164) and dental hygienists (n=93) in their web survey felt they were not aware of best strategies to help patients reduce heavy drinking. 37 A survey of 210 dentists in a large dental practice research network found that the most commonly reported barrier (81%) to addressing alcohol in dental practice was lack of knowledge. 29 Finally, Shepherd et al found that the best predictor of intention to provide alcohol advice was self-eficacy or conidence in the practitioner's ability to intervene with a patient's alcohol use.…”
Section: Discussionmentioning
confidence: 99%